Integrated Marketing Communication To Develop Brand Identity In Fashion Business Case Study: Animal Days (The Indonesian Journal of Business Administration, 2021)
The online fashion industry in Indonesia growing rapidly, especially for clothing brand. Especially in the digital era like now that can facilitate people to make buying and selling via online. So, many MSME are making use of this by selling fashion products online. Based on this, a new clothing brand like Animal Days must have the right strategy in order to compete with its competitors. In this research, Animal Days as a new brand wants to develop the brand identity by using kapferer brand identity prism analysis through Integrated Marketing Communication. This research uses quantitative method to analyze whether the brand identity of Animal Days is in accordance with the market or not by using questionnaire. From the result, Animal Days has to evaluate the brand identity on several factors. This research uses Integrated Marketing Communication (advertising, sales promotion, event & experience, public relations, direct marketing, word of mouth) to develop brand identity of Animal Days. In order for this strategy can be realized, this research also creates an implementation plan in the form of a time line so that the plans that have been made can be more focused.Keywords: brand, brand identity, integrated marketing communication, fashion, clothing brand